2022
DOI: 10.14254/2071-789x.2022/15-3/15
|View full text |Cite
|
Sign up to set email alerts
|

Measuring organisational well-being and happiness based on GNH logic

Andrea Bencsik

Abstract: Among the indices used to measure organisational success, soft factors` role has become more important. Among these, well-being and organisational happiness are particularly important and are becoming more prominent in light of the pandemic. Their measurement is a challenge for management, as the available methods/indices developed in previous years, only partially cover the areas to be assessed. The aim of our research is to find an indicator that allows measuring employee satisfaction, well-being and happine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, a significant number of studies were identified that apply work stress models or investigate employee health in various specific contexts through empirical studies (Hornyák, 2019;Gál-Inges & Németh, 2015). In addition, we found a separate group of studies discussing methods, viability, and measurements of workplace health promotions (Bencsik, 2022;Gorgenyi-Hegyes et al, 2021;Szabó & Juhász, 2019a;Szabó & Juhász, 2019b;Péter et al, 2015), with a significant part of this literature focusing on the impact of physical activity and sport (Ács et al, 2020;Laczkó et al, 2022).…”
Section: Studies and Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significant number of studies were identified that apply work stress models or investigate employee health in various specific contexts through empirical studies (Hornyák, 2019;Gál-Inges & Németh, 2015). In addition, we found a separate group of studies discussing methods, viability, and measurements of workplace health promotions (Bencsik, 2022;Gorgenyi-Hegyes et al, 2021;Szabó & Juhász, 2019a;Szabó & Juhász, 2019b;Péter et al, 2015), with a significant part of this literature focusing on the impact of physical activity and sport (Ács et al, 2020;Laczkó et al, 2022).…”
Section: Studies and Articlesmentioning
confidence: 99%
“…At the same time, it is interesting to note, that the date of the first publication of the model is identical with the Workplace Psychosocial Safety Climate Model (Dollard & Bakker, 2010), and there is a significant overlap between the central concepts of the two models (Psychosocial Environment/Risk, Resources and Engagement). The WHO model, however, offers an expanded scope and an improved applicability to the development of pragmatic organizational interventions and health promotion programs (Bencsik, 2022;Gorgenyi-Hegyes et al, 2021;Szabó & Juhász, 2019a;Szabó & Juhász, 2019b).…”
Section: Studies and Articlesmentioning
confidence: 99%
“…[10][11][12] Similarly, professionals or students might experience varied happiness sources, warranting diverse measurement tools aligned with specific influencing factors. 3,[13][14][15] To cater to these varied segments, a myriad of happiness measurement instruments have been formulated. These tools, customized for distinct demographics like workers, caregivers, adolescents, or even cultural backgrounds, ensure nuanced assessments.…”
Section: Introductionmentioning
confidence: 99%